Parallels of structural-functional parameters the myocardium, C-type natriuretic peptide and endothelin-1 plasma concentrations in women with uncomplicated essential hypertension - V. V. Petrovska; B. M. Zhebel (Zaporozhye State Medical University, 2014)
The development of endothelial dysfunction (DE)plays an important role in the pathogenesis of essential hypertension (EH). Processes of vascular wall remodeling (hyperplasia and hypertrophy of smooth muscle cells of the media, fibrosis) cause progression and stabilization of arterial hypertension [7] and lead to the development of cardiac dysfunction with its subsequent remodeling. From this point of view the study of plasma concentrations of vasodilator-natriuretic peptide C and its direct antagonist endothelin-1 is an important task. Objective: to study plasma concentrations of SNP and ET-1 at changes in state infarction in women ofpostmenopausal age, residents of Vinnytsia region suffering from uncomplicated essential hypertension. Materials and methods. 101 Womenhave been examined, patients with essential hypertension, aged from 45 to 65, all are residents of Vinnytsia region. 51 Patients have GC stage I and other 50 stage II -HH. The control group was formed by 80 women without any cardio - vascular diseases. The selection of subjects was carried out on the basis of detailed history taking and examination using standard clinical, laboratory and instrumental methods of examination. We useddaily monitoring of blood pressure, heart ultrasound, ELISA. Land Survey SNP level, ET-1 and SNP / ET-1 has been determined according to the methodology MU Antamonova. The data has been processed using a standard statistical package Statistica 6,0. Results. According to received information plasma concentrations of SNP and ET-1 in female patients with EH of postmenopausal age were significantly higher than in healthy women of this age, while in patients with essential hypertension stage II plasma levels in their blood were significantly higher than the GC and stage (p <0.01). That level of SNP and ET-1 are associated with the severity of GC. To assess the balance of activity of vasodilators, vasoconstrictors in plasma can be used in ratio SDA / ET-1 (utility model №72156). It has been established that at any stage of GC value ratio SDA / ET-1 was lower than in the control group. In addition, the rate of SNP / ET-1 is higher in GC II. In the analysis of structural and functional changes of the myocardium in patients with essential hypertension it has been found that higher plasma concentration of SNP as ET-1 in patients with essential hypertension stage II is associated with registration of pronounced degree of hypertrophy and the presence of DD. For auxiliary diagnosis of diastolic dysfunction in echocardiographic screening examinations for women of postmenopausal age of patients with essential hypertension stage II residents Vinnytsia region boundary level of SNP, ET-1, and the coefficient of SNP / ET-1 have been calculated. Conclusions. 1.Higher levels of SNP and ET-1 in plasma of women with stage II essential hypertension associated with severe left ventricular hypertrophy. Determined boundary level of SNP, ET-1 and the correlation coefficient of SNP / ET-1 in plasma can be used for screening echocardiography examinations and to the impossibility of ultrasonography for estimated LV diastolic function in women of postmenopausal age with stage II GC . Further rate of SNP / ET-1 may be used to assess balance of vasodilators, vasoconstrictors in blood plasma.